Eyes wide open: exploring men’s and women’s self-reported and physiological reactions to threat and crime - Noon, Michelle S. (Journal of experimental criminology, 2019)
In response to calls for physiological measurement of people's fear of crime, we explored how men and women responded to self-report and physiological measures as they viewed threatening and/or crime-related images.